Políticas de assistência estudantil da Universidade Federal de Santa Maria/RS: estratégias de permanência do estudante na educação superior - Pozobon, Luciane Leoratto (2019)
The present study shows the research on Professional Master’s degree developed on Superior and Basic Education Policies and Management, of the Post-Graduation Program on Public Policies and Educational Management of UFSM. The dissertation intends to answer the following question: Which are the permanence strategies of the college student offered by the students’ assistance of UFSM. It aims at recognizing the permanence strategies of the college student offered by the actions of students’ assistance of UFSM. It also establishes as specific goals: researching about the Students’ Assistance of UFSM; investigating if the actions taken actually influence the permanence of the student in vulnerable socioeconomic situation; finding out the students’ opinion about the Students’ Assistance actions and finally proposing an assessment instrument of the student dropout risk and a service to follow the permanence of the students with socioeconomic benefit. The study begins by mapping of the scientific production and significative debates concerning the proposed theme. The methodology is made up of a mixed qualitative-quantitative approach with documental bibliographic and case study analyses, the theoretical reference was organized from the study of access policies and permanence in college education, the studies about the university students and their permanence in college. A questionnaire based on The College Persistence Questionnaire, developed by Davidson, Beck e Milligan (2009) was applied in order to build the data. The instrument also counted on open questions where the students were able to express what they think about the Students’ Assistance, its role in their permanence in the institution, besides demographic data. It is notorious in the results the importance of Student Assistance for students with socioeconomic benefit, mainly when it concerns material assistance. Moreover, according to the data students do believe that the SA fulfils its objectives. Nevertheless, it is still possible to understand, according to the answers, that the students who consider the Students’ Assistance not sufficient and they criticize the way it is effective in the institution, mainly about the management of student housing, the investment in scholarships, the little publicity given to Students’ Assistance, the lack of professionals and actions aiming at understanding the demands about mental health. Such results are important to think about new and better strategies of intervention to these students. Therefore, at the end of the research, we presented a risk assessment evaluation of the dropout of students with socioeconomic benefit and a service to follow the permanence of such students in socioeconomic vulnerability situation, aiming at contribute for their permanence and helping them finish college.